ABC of heart failure - Gibbs, Christopher R.; Davies, Michael K.; Lipp, Gregory Y. H. (ABC series, 2003)
Evidence shows that the diagnosis and treatment of heart failure is often sub-optimal. The ABC of Heart Failure provides coherent and concise information on epidemiology, pathophysiology, clinical features and the latest advances in this important condition.Edited and written by leading authorities, chapters include: clinical features and complicationsnon-drug management; management of heart failure with ACE inhibitors, diuretics, and nitrates; management of heart failure with digoxin and other inotropes, B-blockers, antiarrhythmic agents and antithrombotic treatment; acute and chronic management strategies; heart failure in general practice. The ABC of Heart Failure will be a valuable resource in the management of heart failure for GPs and hospital doctors.